CĂRŢILE ELECTRONICE ŞI VOCEA UTILIZATORILOR - COSTIN, sociolog, Departamentul dezvoltare şi comunicare, BM „B.P. Hasdeu”, Nadejda (BIBLIOPOLIS, 2020)
This paper presents the results of a cantitative sociological research Perception and satisfaction of young people from a modern library concerning the current of ebooks reading and the position of young people on the services of lending ebooks in the library. The mobile web pushed the library to examine and to implement the new ways of traditional services. A such service – lending of ebooks on ereader - was implemented in the month of November at the Municipal Library B.P. Hasdeu. This service is destinated to the community was conceptualized in several stage by the Municipal Library team and can be consedered as a result of large professional discussions about the ebooks during the Annual conference of Municipal library in 2013.